The Effect of Workaholism on Turnover Intention through Burnout among Generation Z Employees in Yogyakarta - Felisa Indah Sari; Immawan Muhajir Kadim; Muhibbuddin Muhibbuddin (Scimadly Publishing, 2026)
This study aims to analyze the effect of workaholism on turnover intention and examine the moderating role of burnout among Generation Z employees in the Special Region of Yogyakarta. The study employed a quantitative approach with an associative causal research design. Data were collected from 150 Generation Z employees using a purposive sampling technique. The research instrument was distributed through an online questionnaire using a five-point Likert scale. Data analysis was conducted using PLS-SEM. The results showed that workaholism has a positive and significant effect on turnover intention. In addition, burnout was found to have a positive and significant effect on turnover intention. The moderating test results revealed that burnout significantly strengthens the relationship between workaholism and turnover intention among Generation Z employees. These findings indicate that employees who excessively engage in work are more likely to develop turnover intention when they experience higher levels of burnout. This study contributes theoretically to the literature on organizational behavior and human resource management, particularly in understanding the psychological dynamics of Generation Z employees in modern workplaces. Practically, the findings suggest that organizations should implement strategies that support employee well-being, mental health, and work-life balance in order to reduce burnout and minimize turnover intention.